ROZWIJANIE ROZUMIENIA PUBLICYSTYCZNYCH AUDYCJI RADIOWYCH: SPECYFIKA ETAPU POPRZEDZAJĄCEGO SŁUCHANIE - Górecka, Joanna; Wojciechowska, Bernadeta (Neofilolog, 2019)
The paper focuses on the development of the listening comprehension of advanced students of French as a foreign language and concerns current affairs radio programs. It presents the main conclusions discussed with reference to one of the problems researched within a larger academic project conducted from 2010 to 2013. The aim of the paper is to determine some essential principles that should guide the development of questions in the pre-listening stage so that, during the subsequent while-listening stage, they could foster the individual comprehension process. The conclusions emphasize the relationship between the form and function of these pre-listening stage questions and the quality of cognitive and communicative actions performed by the listeners.